The critical success factors of Malaysian Agriculture, Horticulture and Agrotourism Show 2010/Noor Ashekin Mansor - Mansor, Noor Ashekin (Faculty of Business and Management, 2011)
This study is mainly about the Critical Success Factor of Malaysian Agriculture,Horticulture and Agrotourism Show (MAHA) 2010 program. This study was conducted to measure the factor that contribute to the successfulness of the MAHA program.The purpose of this study is more focusing on to analyzing and identify the relationship among the factor of the successfulness of MAHA 2010 performance. The respondents for this study consist of the staff of Federal Agricultural Marketing Authority (FAMA) Pahang.The data from this research was collected by the questionnaire that given to the respondents. Then the data were analyzing using reliability analysis, frequency analysis, Pearson’s correlation coefficient, multiple linear regressions, means and Kruskal-Wallis. Based on the correlations coefficient analysis, it shows that all the three independent variables have significant relationship with the dependent variables which are MAHA performance.Based on the result of multiple linear regressions and means; it shows that teamwork become the most significant predictor with (MAHA) performance. Other than that, this study also to provide recommendations in order to improve the MAHA performance.